The effects of intravenous dexmedetomidine premedication on induction of anaesthesia using target-controlled infusion of propofol and remifentanil - Ab Aziz, Siti Nur Amani (2016)
Objective: The aims of this study were to determine the effects of intravenous dexmedetomidine premedication on induction of anaesthesia and intubation using TCI propofol and TCI remifentanil. Methods: 54 respondents, aged 18 to 60 year-old, ASA I – II patients scheduled for elective surgeries under general anaesthesia with endotracheal intubation were enrolled in this prospective, randomized, observer blinded, controlled clinical trial. They were randomly allocated into two groups. Group I: Dex Group (n=27) received infusion loading dexmedetomidine 1 mcg/kg over ten minute. Group II: Control Group (n=27) received the same calculated volume of 0.9% normal saline solution over ten minute. General anaesthesia was induced in both groups with TCI remifentanil starting at 2 ng/ml over one minute followed by TCI propofol at target plasma concentration of 2 mcg/ml. After one minute, the TCI propofol will be titrated every 0.5 mcg/ml in every 30 second until loss of consciousness achieved. After successful induction, intravenous rocuronium 0.9 mg/kg was given and intubation done after one minute. After intubation, TCI remifentanil must be tapper up by 1 ng/ml if there were any tachycardia and hypertension until stable. The following data were recorded; target plasma concentration and effect-site concentration of propofol atsuccessful of induction, the induction time from starting of TCI propofol to loss of consciousness and any supplementation of TCI remifentanil after intubation. The following parameters were recorded; blood pressure (BP), mean arterial pressure (MAP), heart rate (HR) and bispectral index score (BIS) at T baseline, T after completed loading drug study, T after TCI remifentanil, T after successful TCI propofol, T before intubate, T 1 minute after intubate and T 5 minute after intubate. Results: Dex Group showed significantly lower target plasma concentration of propofol than control group [2.44 (0.54) vs 4.20 (1.11) mcg/ml; p<0.001]. The effect-site concentration of propofol also significantly lower in Dex Group than control group [1.60 (0.67) vs 3.43 (1.09) mcg/ml; p<0.001]. Dex Group had significantly shorter induction time compared to control group [71.59 (38.13) vs 182.48 (62.64) second; p<0.001]. During induction of anaesthesia, there was a significant difference of mean MAP between the two groups based on time; (F=35.64, p<0.001). Mean of MAP in Dex Group was significantly lower than control group at T after TCI remifentanil; [85.93 (CI 95% 80.85, 91.01) vs 94.89 (CI 95% 89.81, 99.97) mmHg]. In term of HR on induction, there were significant differences between the groups (p=0.002) regardless of time and within-between the group based on time (F=22.38, p<0.001). Mean of HR in Dex Group was significantly lower than control group at T after intravenous loading dex; [64.48 (CI 95% 59.94, 69.03) vs 81.22 (CI 95% 76.68, 85.79) bpm] and at T after TCI remifentanil; [64.00 (CI 95% 59.16, 68.83) vs 79.37 (CI 95% 74.53, 84.21) bpm]. After endotracheal intubation, there were significant differences of mean MAP between the two groups (p<0.001) regardless of time. In term of HR after endotracheal intubation, there were significant differences of mean HR between the two groups (p=0.004) regardless of time. The BIS core was significantly lower in Dex Group compared to control group after intravenous loading of dexmedetomidine, [87.83 (7.06) vs 97.70 (0.47); p<0.001]. In term of the BIS score changes there was a significant difference of mean BIS score within-between the two groups based on time (F=22.40, p<0.001). Mean of BIS score in Dex Group was significantly lower than control group at T after intravenous loadingdexmedetomidine; [87.36, (CI 95% 85.75, 89.90) vs 97.71 (95.68, 99.74)] and at T after TCI remifentanil; [83.61 (CI 95% 79.96, 87.26) vs 95.38 (CI 95% 91.80, 98.95)]. Mean of BIS score in Dex Group was significantly higher than control group at T after successful induction; [72.04 (CI 95% 67.65, 76.44) vs 63.46 (CI 95% 59.16, 67.76)] and at T 5 minute after intubation; [54.00 (CI 95% 49.36, 58.64) vs 41.54 (CI 95% 37.00, 46.08)]. No other significant different seen in other parameter; mean of MAP between the two groups and mean of HR within-between the group during induction of anaesthesia, mean HR within-between the group after endotracheal intubation and mean BIS score between the two groups. Summary: Premedication of dexmedetomidine reduced the requirement of target plasma concentration and effect-site concentration of TCI propofol for induction. It also produced shortened induction time and more stable haemodynamic changes during induction, as well as intubation.